1999
DOI: 10.1083/jcb.145.7.1341
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Chromatin Unfolding and Remodeling Induced by VP16 Acidic Activation Domain

Abstract: Analysis of the relationship between transcriptional activators and chromatin organization has focused largely on lower levels of chromatin structure. Here we describe striking remodeling of large-scale chromatin structure induced by a strong transcriptional activator. A VP16-lac repressor fusion protein targeted the VP16 acidic activation domain to chromosome regions containing lac operator repeats. Targeting was accompanied by increased transcription, localized histone hyperacetylation, and recruitment of at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
339
4
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(373 citation statements)
references
References 64 publications
(90 reference statements)
28
339
4
1
Order By: Relevance
“…Results presented here indicate that the high levels of histone acetylation mediated by VP16, and its ability to recruit ATP-dependent chromatin remodeling complexes and histone acetyltransferases (65)(66)(67), are sufficient to fully abrogate the spreading of SIR complexes. In this assay, VP16 acts to increase histone acetylation on both sides of its binding site, thereby activating nearby genes irrespective of their location relative to the telomere, as expected from a local increase of HAT concentration.…”
Section: Discussionmentioning
confidence: 93%
“…Results presented here indicate that the high levels of histone acetylation mediated by VP16, and its ability to recruit ATP-dependent chromatin remodeling complexes and histone acetyltransferases (65)(66)(67), are sufficient to fully abrogate the spreading of SIR complexes. In this assay, VP16 acts to increase histone acetylation on both sides of its binding site, thereby activating nearby genes irrespective of their location relative to the telomere, as expected from a local increase of HAT concentration.…”
Section: Discussionmentioning
confidence: 93%
“…For example, a pioneering study of in vivo dynamics of a 90 Mbp heterochromatin insertion revealed that its transcriptional activation involves a physical transition from a 1 mM compact globule in the nucleus to an intricate web of ®bers that spans 410 mM (Tumbar et al, 1999). It is extremely likely that such transitions involve chromatin remodeling and modi®-cation engines and, in fact, large chromatin domains have been seen`partly' remodeled (`unfolded'?)…”
Section: No Conclusionmentioning
confidence: 99%
“…While its elementary particle, the nucleosome (Kornberg and Thomas, 1974), is ubiquitous (Noll, 1974), chromatin over a given DNA locus can assume a great variety of markedly distinct structural states in vivo (Hebbes et al, 1994(Hebbes et al, , 1988Tumbar et al, 1999;Wu, 1980;Zaret and Yamamoto, 1984): after all, many di erent buildings can be created using the same bricks. There is very strong correlative evidence connecting chromatin structure of a speci®c locus and the level of its transcriptional activity (for example, in addition to the studies just cited, Bone et al, 1994;Braunstein et al, 1993;Jeppesen and Turner, 1993;Kuo et al, 1998).…”
Section: Twist and Writhe: How Chromatin Gets Goingmentioning
confidence: 99%
“…Additional studies are needed to determine whether similar results will be obtained with transgenes inserted at other chromosomal locations and in nuclei from other cell types. Interphase chromosomes might also change their positions during development or under various inducing or environmental stress conditions (Tumbar et al, 1999;Dietzel et al, 2004). The ability to view the fluorescence-tagged loci in living cells provides a means to study these and other problems of interphase chromosome organization.…”
Section: Movement Of Chromosomesmentioning
confidence: 99%